Occurrence of clubroot and Plasmodiophora brassicae Wor. races in Finland - Annikki Linnasalmi; Anneli Toiviainen (Scientific Agricultural Society of Finland, 1991)
Examination of clubroot in cruciferous vegetables in Finland in 1974—1978 revealed the disease in 81 % of the 101 communes inspected. The disease was most common in southern and central Finland, but was also discovered in the northern parts of the region in which cruciferous crops were cultivated (66 —67° N. lat.). Clubroot was found in 65 % of the 375 plant samples collected. It occurred in 68 % of the samples of the most commonly cultivated vegetable, cabbage (56 % of the material), in 63 °Jo of the cauliflower samples (22 % of the material), in 56 % of the samples of other cole species (13 % of the material) and in 64 % of the samples of cruciferous root crops (10 % of the material). P. brassicae race determinations were performed on 90 samples. The classification system of Williams (1966) was applied. The races that were isolated were 1,2, 3,4, 6 and 7. Race 2 was by far the most common, being found in 32 communes; races 3,4, 6 and 7 were each found in 9—12 communes; race 1 only in one commune. No clear differences in the occurrence of the races in the various parts of the country could be observed. A comparison is made between Williams’ and the ECD (Buczacki et al. 1975) classification systems. In addition, the pathotypes in clubroot material from Norway and Iceland were determined.